2022
DOI: 10.3390/cancers14061589
|View full text |Cite
|
Sign up to set email alerts
|

The Barcelona Predictive Model of Clinically Significant Prostate Cancer

Abstract: A new and externally validated MRI-PM for csPCa was developed in the metropolitan area of Barcelona, and a web-RC designed with the new option of selecting the csPCa probability threshold. The development cohort comprised 1486 men scheduled to undergo a 3-tesla multiparametric MRI (mpMRI) and guided and/or systematic biopsies in one academic institution of Barcelona. The external validation cohort comprised 946 men in whom the same diagnostic approach was carried out as in the development cohort, in two other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Medians and interquartile ranges (25-75 percentiles) were used to describe the quantitative variables, and rates were used to describe the qualitative variables. The MRI-PMbdex individual likelihoods of csPCa were generated from the logistical regression analysis performed from the included independent predictors of the Barcelona MRI-PM [38]. The mPSAD individual likelihoods of csPCa were generated from the logistic regression analysis performed from the following independent predictors: PI-RADS score and mP-SAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medians and interquartile ranges (25-75 percentiles) were used to describe the quantitative variables, and rates were used to describe the qualitative variables. The MRI-PMbdex individual likelihoods of csPCa were generated from the logistical regression analysis performed from the included independent predictors of the Barcelona MRI-PM [38]. The mPSAD individual likelihoods of csPCa were generated from the logistic regression analysis performed from the following independent predictors: PI-RADS score and mP-SAD.…”
Section: Discussionmentioning
confidence: 99%
“…MRI-PMbdex was created from the development cohort of 1486 men studied at Vall d'Hebron Hospital (VHH) and the external validation cohort of 946 men from Parc de Salut Mar (PSM) as well as Hospital Germans Trias i Pujol (GTiPH). This study was conducted between January 1, 2006, and 31 December 2019 [38]. Pre-biopsy 3-Tesla mpMRI and guided or systematic prostate biopsies were always performed.…”
Section: Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Barcelona RC incorporates the new option of selecting the proper risk threshold and it is the first to analyse risk according to PI-RADS categories. The authors concluded that the global efficiency of RCs does not translate to a true utility for each PI-RADS category [5] .…”
mentioning
confidence: 99%
“…The Barcelona RC was designed, after MRI-PM development and external validation, using data for 2486 men with suspected PCa from the Barcelona metropolitan area, with csPCa (grade group ≥2) detection of 37.6% [5] . The Barcelona RC uses the same predictors as the Rotterdam MRI-RC in addition to PCa family history and PI-RADS v.2 ( https://mripcaprediction.shinyapps.io/MRIPCaPrediction/ ).…”
mentioning
confidence: 99%